2006
DOI: 10.1002/chem.200501574
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Allylic Substitution Catalyzed by C1‐Symmetrical Complexes of Molybdenum: Structural Requirements of the Ligand and the Stereochemical Course of the Reaction

Abstract: Application of new chiral ligands (R)-(-)-12 a and (S)-(+)-12 c (VALDY), derived from amino acids, to the title reaction, involving cinnamyl (linear) and isocinnamyl (branched) type substrates (4 and 5 --> 6), led to excellent regio- and enantioselectivities (>30:1, < or =98 % ee), showing that ligands with a single chiral center are capable of high asymmetric induction. The structural requirements of the ligand and the mechanism are discussed. The application of single enantiomers of deuterium-labeled substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 88 publications
1
33
0
3
Order By: Relevance
“…[259] Very recently, C 1 -symmetric pyridine-substituted diamine (S)-(+)-L194 was shown to be an efficient chiral ligand for the molybdenum-catalyzed asymmetric allylic alkylation of dimethyl malonate with isomeric carbonate 92 a and 269: the branched product 110 b was afforded with excellent regioand enantioselectivities (> 30:1, 97-98 % ee, Scheme 87). [260] 4. Iridium-Catalyzed Enantioselective Allylation The reaction of 5-phenyl-1-penten-3-yl acetate (94 f) with sodium malonate in the presence of chiral ligand L195 afforded the branched product (R)-271 a with 93 % ee and high regioselectivity.…”
Section: Methodsmentioning
confidence: 99%
“…[259] Very recently, C 1 -symmetric pyridine-substituted diamine (S)-(+)-L194 was shown to be an efficient chiral ligand for the molybdenum-catalyzed asymmetric allylic alkylation of dimethyl malonate with isomeric carbonate 92 a and 269: the branched product 110 b was afforded with excellent regioand enantioselectivities (> 30:1, 97-98 % ee, Scheme 87). [260] 4. Iridium-Catalyzed Enantioselective Allylation The reaction of 5-phenyl-1-penten-3-yl acetate (94 f) with sodium malonate in the presence of chiral ligand L195 afforded the branched product (R)-271 a with 93 % ee and high regioselectivity.…”
Section: Methodsmentioning
confidence: 99%
“…(39)]. [116] A weak (+)-NLE was detected when scalemic 143 was employed. Since previous crystallographic studies indicated that the active intermediate in such reactions was a monocoordinated allylic complex [Mo(CO) 2 L(allyl)], [117] the authors suggested an equilibrium between the active Mo(L) and inactive (Mo) n (L) 2 complex (n = 1 or 2), which serves as a racemic trap.…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…[259] Das C 1 -symmetrische pyridylsubstituierte Diamin (S)-(+)-L194 erwies sich erst kürzlich als effizienter chiraler Ligand in der molybdänkatalysierten asymmetrischen allylischen Alkylierung der isomeren Carbonate 92 a und 269 mit Dimethylmalonat, die mit ausgezeichneter Regio-und Enantioselektivität (> 30:1, 97-98 % ee) zum verzweigten Produkt 110 b führte (Schema 87). [260] 4. Iridiumkatalysierte enantioselektive Allylierungen [261] Iridiumkomplexe mit chiralen Liganden wie dem Phosphan-Oxazolin L196, [262] (S)-1,1'-Binaphthyl-2,2'-diylphenylphosphit L197, [263] oder den Phosphoramiditen L198 [264] [272] Han et al haben kürzlich die Synthese der Allylamine 282 (70-92 % Ausbeute, 92 bis über 99 % ee) durch regio-und enantioselektive decarboxylierende allylische Amidierung der Allylbenzylimidodicarbonate 281 beschrieben (Schema 91).…”
Section: 3-dienylierungen Von 2-brom-13-dienenunclassified